A hybrid superconcentrated electrolyte enables 2.5 V carbon-based supercapacitors. Issue 57 (15th June 2020) - Wang, Weijian; Deng, Wenjun; Wang, Xusheng; Li, Yibo; Zhou, Zhuqing; Hu, Zongxiang; Xue, Mianqi; Li, Rui
Abstract : A hybrid electrolyte with a 5.3 V electrochemical window enables 2.5 V carbon-based supercapacitors. Abstract : A hybrid solvent in salt electrolyte was developed by hybridizing aqueous and organic solvents in concentrated lithium bis(fluorosulfonyl)imide (LiFSI) salts, such an electrolyte provides an unprecedented electrochemical window of 5.35 V, which is even comparable to traditional organic electrolytes, and enables a super-stable carbon-based symmetric supercapacitor with a long life of 10 000 cycles at an operating voltage of 2.5 V.